An Optical Wavelength Measurement Technique Using Erbium-Doped Fiber Attenuation - Affandi, Norhayati (2003)
The widespread deployment of optical fiber with its attractive technologies such as dense wavelength division multiplexing (DWDM) is helping to satisfy the apparently insatiable demand for bandwidth in the telecommunication systems.However,the adoption of the technology in the optical communications systems,requires the establishment of traceable measurement facilities,which are capable of providing the information about the performance of the system. Information of particular parameter of interest, such as channel wavelength,can be obtained by either using an external or inline or built-in wavelength determination system.Currently,there are a number of techniques including bandpass filter technique, and interferometric fringe-counting techniques have been used in the system to measure the wavelength accurately.In this thesis,a new approach for measuring optical signal wavelength using optical fiber power loss phenomenon is introduced. In this technique a relationship between input signal at one particular wavelength and attenuated signal in optical fiber is used.A wavelength dependent attenuator made of erbium-doped fiber has been used as the main component or element to develop and be applied for the wavelength determining system.The variation of the optical power loss of erbium-doped fiber with the wavelength of an input signal is utilized for wavelength discrimination.This research demonstrates some of the methods that can be used to exploit the erbium-doped fiber for measuring optical signal wavelength accurately.Results of the study showed that by changing parameter such as value of attenuation element,erbium-doped fiber length, ion concentration,or the erbium-doped fiber material type,or changing the attenuation element setup, the signal measurement could be as accurate as ± 2 nm and produce a wavelength range as wide as 45 nm.